The Harvey girls [videorecording (DVD)] - Garland, Judy; Hodiak, John; Bolger, Ray; Lansbury, Angela, 1925-; Adams, Samuel Hopkins, 1871-1958 (Archive collection., 2017)
On a train trip West to become a mail order bride, Susan Bradley meets a cheery crew of young women traveling out to open a "Harvey House" restaurant at a remote whistle stop to provide good cooking and wholesome company for railway travelers. When Susan and her bashful suitor find romance daunting, Susan joins the Harvey Girls instead. The saloon across the street with its alluring worldly-wise women offers them tough competition, fair and foul, and Susan catches the eye of the Ned Trent, the distant but intense proprietor of the bar --IMDb.